Genetic Risk for Inflammatory Bowel Disease Is a Determinant of Crohn's Disease Development in Chronic Granulomatous Disease. Issue 12 (8th November 2016) - Huang, Chengrui; De Ravin, Suk See; Paul, Adam R.; Heller, Theo; Ho, Nancy; Wu Datta, Lisa; Zerbe, Christa S.; Marciano, Beatriz E.; Kuhns, Douglas B.; ,; Kader, Howard A.; Holland, Steven M.; et al.
Abstract : Background: Approximately, one-third to one-half of children with chronic granulomatous disease (CGD) develop gastrointestinal inflammation characteristic of idiopathic inflammatory bowel disease (IBD), usually Crohn's disease. We hypothesized that the overall IBD genetic risk, determined by IBD genetic risk score (GRS), might in part determine IBD development in CGD. Methods: We reviewed medical records to establish IBD diagnoses in CGD subjects seen at NIAID. IBD risk single nucleotide polymorphism genotypes were determined using the Immunochip, and GRS were estimated by Mangrove. Results: Among 157 white patients with CGD, 55 were confirmed, 78 excluded, and 24 were uncertain for IBD. Two hundred one established, independent European IBD risk single nucleotide polymorphisms passed quality control. After sample quality control and removing non-IBD CGD patients with perianal disease, mean GRS for 40 unrelated patients with CGD-IBD was higher than 53 CGD non-IBD patients (in log2 -scale 0.08 ± 1.62 versus −0.67 ± 1.64, P = 0.026) but lower than 239 IBD Genetics Consortium (IBDGC) young-onset Crohn's disease cases (0.76 ± 1.60, P = 0.025). GRS for non-IBD CGD was similar to 609 IBDGC controls (−0.69 ± 1.60, P = 0.95). Seven established IBD single nucleotide polymorphisms were nominally significant among CGD-IBD versus CGD non-IBD, including those near LACC1 ( P = 0.005), CXCL14 ( P = 0.007), and TNFSF15 ( P = 0.016). Conclusions: The weight of the common IBD risk alleles are significant determinants of IBD in CGD. However, IBD risk gene burden among CGD children with IBD is significantly lower than that in nonsyndromic pediatric Crohn's disease, congruent with the concept that defective superoxide production in CGD is also a major IBD risk factor. Individual IBD genes might interact with the CGD defect to cause IBD in CGD.